Vicky Foskolou and Sophia Kalopissi-Verti (eds) Intercultural Encounters in Medieval Greece after 1204: The Evidence of Art and Material Culture. Byzantios: Studies in Byzantine History and Civilization. - Carr , Mike (Journal of Greek Archaeology, 2024)
The origins of this volume can be traced back to a roundtable discussion on the archaeological and artistic evidence for interrelations between Latins and Greeks in post-1204 Greece and the Aegean, held at the 23rd International Congress of Byzantine Studies, in Belgrade in 2016. Despite recent advances in the field, the art and material culture of medieval Greece have been studied in a rather piecemeal fashion, and the roundtable discussion highlighted the need for a more unified approach to the question of cross-cultural interactions, which is what the present volume aims to achieve. Indeed, in bringing together fourteen chapters on various aspects of artistic production, architecture and archaeology, including contributions on understudied areas, such as song and music, and dress and fashion, the volume certainly succeeds in this endeavour.